Advances in optogenetic studies of depressive-like behaviors and underlying neural circuit mechanisms - Lin, Shanshan; Du, Yiwei; Xia, Yujie; Xie, Yumeng; Xiao, Ling; Wang, Gaohua (Frontiers in Psychiatry, 2022)
Backgrounds: The neural circuit mechanisms underlying depression remain unclear. Recently optogenetics has gradually gained recognition as a novel technique to regulate the activity of neurons with light stimulation. Scientists are now transferring their focus to the function of brain regions and neural circuits in the pathogenic progress of depression. Deciphering the circuitry mechanism of depressive-like behaviors may help us better understand the symptomatology of depression. However, few studies have summarized current progress on optogenetic researches into the neural circuit mechanisms of depressive-like behaviors. Aims: This review aimed to introduce fundamental characteristics and methodologies of optogenetics, as well as how this technique achieves specific neuronal control with spatial and temporal accuracy. We mainly summarized recent progress in neural circuit discoveries in depressive-like behaviors using optogenetics and exhibited the potential of optogenetics as a tool to investigate the mechanism and possible optimization underlying antidepressant treatment such as ketamine and deep brain stimulation. Methods: A systematic review of the literature published in English mainly from 2010 to the present in PubMed was performed. The selected literature is then categorized and summarized according to their neural circuits and depressive-like behaviors. Conclusions: Many important discoveries have been made utilizing optogenetics. These findings support optogenetics as a powerful and potential tool for studying depression. And our comprehension to the etiology of depression and other psychiatric disorders will also be more thorough with this rapidly developing technique in the near future.